Integrasi Pendidikan Jasmani, Olah Raga Dan Kesehatan Berbasis Budaya Lokal Sulawesi Selatan - Nur Indah Atifa Anwar; Hasyim; Andi Atsam Mappanyukki (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Physical Education, Sports, and Health (PJOK) is an integral component of the national education system in Indonesia, physical education not only functions to improve the physical fitness of students, but also plays a role in developing character, social skills, and cultural values . The elements of local culture in South Sulawesi that can be integrated into physical education are very diverse. This study uses a qualitative approach with a case study method to explore experiences and views involving 170 students, 90 teachers, and 40 parents of students. Data collection techniques in this study consisted of in-depth interviews, participant observation, and document analysis. 75% of students feel motivated to participate in physical education learning activities. 65% of teachers have integrated local culture. 80% of parents support the implementation of culture-based physical education, the increase in academic achievement of students has increased with an average final exam score increasing by 15% compared to schools that do not apply this approach. The study is expected to provide insight for policy makers and educators in designing a more relevant and sustainable physical education curriculum.